Capacity building for the identification, mitigation, and communication of DURC in Pakistan: A cross-sectional study - Shamsul Arfin Qasmi (KeAi Communications Co., Ltd., 2021)
The increasing threat posed by state and nonstate actors seeking to misuse scientific and technological developments means it is more important than ever to ensure the responsible conduct of life sciences research, biosecurity research, and dual-use research of concern (DURC). Pakistan has a rapidly growing research environment and, being a signatory to the Biological Toxins and Weapons Convention, is committed to raising DURC awareness among its researchers. To this end, a series of five workshops were conducted in Pakistan between July 2018 and January 2020 with the support of the United States organization Health Security Partners. The workshops targeted universities offering postgraduate programs in life and medical sciences. The purpose of the workshops was to enable participants to understand the concept of DURC, review their own research, determine if any of their experiments may be DURC, identify potential risks while conducting the research, and develop protocols to mitigate DURC threats. A pre-and post-workshop questionnaire evaluated the knowledge of the participants. Evaluations of both the course and facilitators were obtained at each workshop.